Lukacs and the issue of democracy as a strategy - Del Roio, Marcos [UNESP] (Ariadna Ediciones & Saint Petersburg State Univ, 2021)
The question of strategy firstly appears on Lukacs' thought on the so-called Blum Theses, written towards the end of 1928 as a formula against bourgeoise domination, further developed between 1945-47, phase of the new democracy as the path for overcoming Capitalism. Lukacs also develops a reflection about socialist democratization as a formula to destroy the bureaucracy that had germinated, becoming power and habit in socialist experiences.
Keywords: democratic dictatorship; new democracy; socialist democratization; Stalinism